Induksi dan Proliferasi Kalus Embriogenik pada Beberapa Genotipe Kedelai - Khumaida, Nurul; Handayani, Tri (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
The successful of gene transformation on crop plants depends on the ability of explant to develop somatic embryos. The effect of medium composition on induction and proliferation of embryonic callus was analyzed on several soybean genotypes, including low irradiance (LI) tolerant genotype (Ceneng, Pangrango C6-30-10 and C6-76-10) and two LI sensitive genotypes (Godeg and Slamet). Immature cotyledons (14 DAA) were cultured in induction medium including MSIA (MS, vitamin B5, 30% sucrose, 0.2% gelrite, 10 mg L-1 2,4-D and 10 mg L-1 NAA) and MSIB (MS, vitamin B5, 30% sucrose, 0.2% gelrite, and 40 mg L-1 2,4-D). Embryonic calli was subcultered one month after initiation onto proliferation medium including MSIIA (MS, vit. B5, 30% sucrose, 0.2% gelrite, 5 mg L-1 2,4-D and 5 mg L-1 NAA) and MSIIB (MS, vitamin B5, 30% sucrose, 0.2% gelrite, and 20 mg L-1 2,4-D). The result showed that percentage of callused explant was 76-94% and the highest initiation obtained on Pangrango genotypes. The average of calli diameter at 1 month after initiation was 0.5-1.2 cm. Calli which was obtained on MSIA medium showed yellow, tranparent, and friable, whereas calli was obtained on MSIB medium showed yellow-brown, transparent, and friable. Increasing calli diameter and structure were obtained on proliferation medium. The combination of 2,4-D and NAA on MSIA and MSIIA both are induction and proliferation medium respectively were better than MSIB and MSIIB which were contain only 2,4-D. Ceneng genotype showed best performance of somatic embryogenesis than others, and Slamet genotype showed lowest response both on callus induction and proliferation. Keywords: immature cotyledons, embryonic callus, NAA, 2,4